2012
DOI: 10.5194/acp-12-10107-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exceedances in the daily PM<sub>10</sub> mass concentration (50 μg m<sup>−3</sup>) at a roadside station in Leipzig, Germany

Abstract: Abstract. Five years of PM 10 and PM 2.5 ambient air measurements at a roadside, an urban, and a regional background site in Leipzig (Germany) were analyzed for violations of the legal PM 10 limit value (EC, 1999). The annual mean PM 10 concentrations at the three sites were well below the legal threshold of 40 µg m −3 (32.6, 22.0 and 21.7 µg m −3 , respectively). At roadside, the daily maximum value of 50 µg m −3 was exceeded on 232 days (13 % of all days) in [2005][2006][2007][2008][2009], which led to a vio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…S9 of the Supplement). Dry deposition is generally largest over regions with large ambient NH 3 concentrations over the Netherlands and Belgium, as also reported in the literature (Flechard et al, 2011). We also predict high nitrogen dry deposition around the Po Valley in northern Italy.…”
Section: Nitrogen Depositionsupporting
confidence: 87%
See 1 more Smart Citation
“…S9 of the Supplement). Dry deposition is generally largest over regions with large ambient NH 3 concentrations over the Netherlands and Belgium, as also reported in the literature (Flechard et al, 2011). We also predict high nitrogen dry deposition around the Po Valley in northern Italy.…”
Section: Nitrogen Depositionsupporting
confidence: 87%
“…rope, which are 120 µg m −3 maximum daily 8 h mean for O 3 and 50 µg m −3 daily mean for PM 10 (Engler et al, 2012;Hettelingh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among all GUAN sites, Leipzig-Mitte exhibits the greatest exposure to traffic-related pollutants. PM 10 mass and ultrafine particle number concentrations were discussed by Engler et al (2012) and Ma and Birmili (2015), respectively. Leipzig-Mitte was added to GUAN for the purpose of monitoring possible changes in ultrafine particle number and eBC mass concentrations along with the introduction of the low-emission zone (Umweltzone) in Leipzig (Rasch et al, 2013;Löschau et al, 2015).…”
Section: Leipzig-mittementioning
confidence: 99%
“…Some studies, however, have suggested that the massbased metrics might not be the most favourable parameter to characterise PM-induced health effects (HEI Review Panel on Ultrafine Particles, 2013). Some epidemiological studies have associated health endpoints with the number of ultrafine particles or the particle surface area rather than particle mass (Ibald-Mulli et al, 2002;Franck et al, 2011;Rückerl et al, 2011). Ultrafine particles are ubiquitous in urban atmospheres (Kumar et al, 2014), and their ability to penetrate deep into the human body after inhalation has been forwarded as a rationale for their adverse health effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an understanding of the finer aerosol concentration in the atmosphere is important. Even though PM10 is of major concern in worldwide environmental issues, such as visibility degradation and air quality assessment (Engler et al 2012), PM2.5 is mostly responsible for health hazards (Jin et al 2006). Fine (PM2.5) particles have longer residence times in the atmosphere and are composed of higher fractions of organic compounds compared to PM10 (Jaenicke 1984).…”
Section: Introductionmentioning
confidence: 99%